Secure and Scalable Microservices Architecture : Principles, Benefits, and Challenges - Dileep Domakonda, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Microservices architecture is one approach to structuring applications as a collection of small, independently deployable services interacting via APIs, which improves modularity, scalability, and fault isolation. Microservices provide better resilience, deployment flexibility, and utilization of resources compared to monolithic architectures, making them a perfect fit for cloud-native applications. In today's paper, we discuss fundamental principles such as independent deployment, decoupling, fault tolerance, and technology agnosticism while considering challenges such as inter-service communication, data consistency, and management of distributed systems. Furthermore, we discuss how microservices improve agility, scalability, and operational efficiency while demanding strong API management and monitoring. The article also discusses real-world deployments, illustrating how companies use microservices to simplify software development, enhance fault isolation, and update applications conveniently. By considering these aspects, companies can migrate from monolithic to microservices-based architectures, which facilitates the efficient deployment, scalability, and management of cloud-based applications in the current era.
Keywords: Microservices; Cloud Computing; API Communication; Scalability; Distributed Systems